Penerapan Model Flipped classroom dalam Pembelajaran Daring pada Mata Kuliah Metode Pembelajaran, Studi Kurikulum, dan Telaah Kurikulum di Universitas Pelita Harapan - Kurniawati Martha; Eben Hezer Zega (TIME in Physics, 2023)
Online learning during a pandemic is a challenge for lecturers in trying to manage interesting learning and can equip students to become skilled people, and able to face the challenges in the future. The practice encountered in class shows online learning that is less active, interactive, and fun, and students who are less enthusiastic, initiative, and responsive. The solution provided by researchers is the application of the flipped classroom model in managing online learning. The aim of the research is to explain the importance of the role of lecturers in managing online learning and to explain lecturers' efforts to make online learning effective using the flipped classroom model. The research methodology used is descriptive qualitative by utilizing the results of observations, assessment results and questionnaires filled out by students supported by literature studies. The implementation of the flipped classroom model was carried out in Curriculum Studies, Learning Methods, and Curriculum Review courses in January - April 2021. The results of the study showed that the flipped classroom model was able to help lecturers manage online learning. In a more effective application, lecturers are advised to get to know students more holistically and continue to develop themselves, so that they can support good learning management.